Eastern Palaearctic Scythrididae (Lepidoptera: Gelechioidea): description of a new genus and some new species - D’entrèves, Pietro Passerin; Roggero, Angela (Zootaxa, 2009)
A new genus, Bactrianoscythris gen. nov., and five new species are described from the eastern Palaearctic Region: Bactrianoscythris afghana sp. nov., B. annae sp. nov., B. drepanella sp. nov., B. khinjani sp. nov. and B. ginevrae sp. nov. Scythris satyrella Staudinger, and S. pamirica Passerin d’Entrèves & Roggero are transferred to the new genus, and genitalic features of B. satyrella are re-described. A key to species of the new genus is provided. Scythris farsi sp. nov., of unknown affinities, is described from Iran. New records extending the known geographical distribution of another 9 species of Scythris and one species of Catascythris are also presented.